Local Cuisine and Tourists Experience in Bali Through Social Media Practices - Komang Ratih Tunjungsari; Dika Pranadipa Koeswiryono (Journal of Business on Hospitality and Tourism, 2018)
Balinese local cuisine has enriched the culinary dictionary for tourists who want to experience the culture and heritage of Bali. Popularity of tourist destination nowadays can be defined by the popularity of the local cuisine as the tourist image brand and image. The purpose of this article is to describe the involvement of local cuisine gradually in tourist experience quality as the integral part of food tourism in Bali. In aims of determining the tourists’ experience in seeking local cuisine and the perception of Balinese local cuisine, specifically nasi campur Bali and ayam betutu in creating food tourism in Bali. In order to develop the exploratory study, the author using exploratory descriptive methodology in this small-scale research. This study is just a beginning and an introduction to the food tourism in Bali although the practices has been experienced long ago before it is written in hospitality literature like nowadays. Keywords: local cuisine, holiday experience, food tourism, social media